Pengembangan Media Maze Board Animal dalam Pembelajaran IPA untuk Siswa Kelas III Sekolah Dasar - Raihanah Raihanah; Novanita Whindi Arini (Universitas Kanjuruhan Malang, 2022)
Maze board animal media development in science learning for third-grade elementary school students. This study aims to develop Maze Board Animal learning media in science learning material for classifying animals based on the type of food in class III. This study also aims to determine the feasibility of Maze Board Animal media products by involving experts in the process of developing and assessing their products. This research uses research and development methods (Research and Development). In this study, researchers conducted product feasibility tests by conducting product trials and t-tests to see student learning outcomes. The product test stage is carried out using the ADDIE model method, namely (Analysis, Design, Development, Implementation, and Evaluation). The instrument used in this study was a questionnaire. The product assessment team consists of media experts, material experts, educational experts, and response students of grade III SD /MI. Research subjects are 20 third class of elementary school students, chosen by using total sampling. Maze Board Animal media is considered effective and suitable for use in the learning process. It is shown by the results of t-test that Maze Board Animal media is effective to increase the result of the study of students (t= 65,35, p<0,05). And the results of media experts obtained an assessment of 91.7%, material experts obtained 88.3%, educational experts 94%, from product test students obtained 95%. From this assessment, the Maze Board Animal media can be used in student learning.